Use of Dissolved Helium as an Environmental Water Tracer - Richter, Florian; Whittier, Robert B; El-Kadi, Aly I (Journal of hydraulic engineering (New York, N.Y.), 2008)
This study deals with the development, calibration, and testing of an automated technology for using helium as a water tracer in continuous real-time monitoring. The instrument combines a gas extraction system and a helium mass spectrometer. The technology was tested in laboratory pipe, open-water, and porous- media experiments, and the results were used to test helium breakthrough curves against those for salinity expressed by electrical conductivity. The instrument promptly responds to concentration changes. In general, accurate results were obtained for first arrival times and peaks of solutes, as well as for the dispersive characteristics of the breakthrough curves. The accuracy of the elution curves needs some improvement due to limitations of the helium extraction system. In addition, the developed method is sensitive to the water flow rate and nitrogen pressure used in extracting helium from the solution. These issues can be addressed through calibration. Potential improvements are possible through the use of more precise helium concentration quantification equipment and through enhancement of the extraction method. The success of the methodology makes helium an attractive tracer for use near drinking water sources, in environmentally sensitive areas such as wetlands and fish farms, and near recreational or other areas where a esthetics are a concern.